Balls left empty by a critical branching Wiener process. (1996) - Révész, Pál
Abstract : At time t = 0 we have a Poisson random field on ℝ d . Each particle executes a critical branching Wiener process starting from its position at time t = 0 . Let R T be the radius of the largest ball around the origin of ℝ d which does not contain any particle at time T . Our goal is to characterize the properties of the stochastic process { R T, T ≥ 0 } . This article is dedicated to the memory of Professor Roland L. Dobrushin.